TEACHER DEVELOPMENT INTENSITY AND RESPONSIBILITY WITH PERFORMANCE IN SENIOR HIGH SCHOOL - Iman Rais Juliawan Galuh; Agus Iwan Mulyanto (JURNAL ILMIAH ILMU ADMINISTRASI, 2021)
Teacher performance affects the intensity relationship between teacher job satisfaction, organizational culture, teacher responsibility, and the intensity of coaching and teacher welfare from the principal. The aim is to see the intensity of coaching and responsibility with the productivity of teacher performance. The research method used in this study is the Crocoational Survey which is associative of the relationship between two or more variables. The data used is quantitative data, namely numerical data in statistical counts that are collected through a research questionnaire from a number of respondents. Validity test such as (a). Classical Assumption Test (b). Hypothesis Test (c). Multiple Linear Regression (d). Correlation Coefficient Test (e). Determination Coefficient Test Conclusion: There is a positive and significant relationship between the coaching intensity variable and teacher performance, and a significant positive relationship between the responsibility variable and the teacher performance variable, as well as a positive and significant relationship between the coaching intensity variable and the responsibility variable with the teacher performance variable. Keywords : Intensity Relationship, Teacher Development, Responsibility, Performance